2017
DOI: 10.1016/j.phrs.2017.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane inhibits platelet-derived growth factor-induced vascular smooth muscle cell proliferation by targeting mTOR/p70S6kinase signaling independent of Nrf2 activation

Abstract: Activation of nuclear factor erythroid 2-related factor 2 (Nrf2, a transcription factor) and/or inhibition of mammalian target of rapamycin (mTOR) are implicated in the suppression of vascular smooth muscle cell (VSMC) proliferation. The present study has examined the likely regulatory effects of sulforaphane (SFN, an antioxidant) on Nrf2 activation and platelet-derived growth factor (PDGF)-induced mTOR signaling in VSMCs. Using human aortic VSMCs, nuclear extraction and siRNA-mediated downregulation studies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 73 publications
4
43
0
1
Order By: Relevance
“…Similar to our results, Yoo et al showed that the electrophile SFN was able to inhibit neointimal hyperplasia in a non-diabetic carotid artery balloon injury model [22]. Shawky and Segar showed that SFN inhibited VSMC proliferation and neointimal hyperplasia in a mouse femoral artery wire injury model [23]. This group has also previously shown that SFN is able to inhibit leptin-induced VSMC proliferation and suppress neointimal hyperplasia in diet-induced obese mice [24].…”
Section: Discussionsupporting
confidence: 90%
“…Similar to our results, Yoo et al showed that the electrophile SFN was able to inhibit neointimal hyperplasia in a non-diabetic carotid artery balloon injury model [22]. Shawky and Segar showed that SFN inhibited VSMC proliferation and neointimal hyperplasia in a mouse femoral artery wire injury model [23]. This group has also previously shown that SFN is able to inhibit leptin-induced VSMC proliferation and suppress neointimal hyperplasia in diet-induced obese mice [24].…”
Section: Discussionsupporting
confidence: 90%
“…In response to vascular injury, the activated in ammatory cells, platelets and SMCs release the growth factors, especially platelet-derived growth factor (PDGF), thereby leading to a switch of SMCs from a contractile phenotype to a synthetic phenotype [48][49][50]. PDGFB is described to be one of the most potent stimulants for SMCs proliferation and migration [51]. In early vascular development, synthetic phenotypic SMCs are required to migrate around lumens, proliferate and secrete extracellular matrix to promote intercellular connections.…”
Section: Discussionmentioning
confidence: 99%
“…The medial area was determined by subtraction of the IEL area from the EEL area (i.e., medial area = EEL area – IEL area) [25]. The cryosectioning, H&E staining, and EVG staining of the injured femoral arteries (from control and treated conditions) were performed in a blinded manner as described earlier [27]. …”
Section: Methodsmentioning
confidence: 99%